2017
DOI: 10.1002/pola.28872
|View full text |Cite
|
Sign up to set email alerts
|

How good is CuAAC “click” chemistry for polymer coupling reactions?

Abstract: ABSTRACT:1 H NMR and SEC analyses are used to investigate the overall efficiency of Copper Catalyzed Azide Alkyne Cycloaddition (CuAAC) "click" coupling reactions between alkyneand azide-terminated polymers using polystyrene as a model. Quantitative convolution modeling of the entire molecular weight distribution is applied to characterize the outcomes of the functional polymer synthesis reactions (i.e., by atom transfer radical polymerization), as well as the CuAAC coupling reaction. Incomplete functionality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…The main advantages of these reactions include their fast reaction kinetics, versatililty and regiospecificity, high product yields, and easy purification of the products. In this regard, these methodologies have been efficiently used along the past decade in the preparation of polymers [ 103 ], but their application in fuel cells remains almost unexplored.…”
Section: Influence Of the Pbi Structure And Synthetic Methods On Imentioning
confidence: 99%
“…The main advantages of these reactions include their fast reaction kinetics, versatililty and regiospecificity, high product yields, and easy purification of the products. In this regard, these methodologies have been efficiently used along the past decade in the preparation of polymers [ 103 ], but their application in fuel cells remains almost unexplored.…”
Section: Influence Of the Pbi Structure And Synthetic Methods On Imentioning
confidence: 99%
“…While the conventional radical termination can be minimized by decreasing the rate of polymerization and by terminating the reaction at lower monomer conversion, suppression of the Glaser coupling remains a challenge. 82,91,92 One of the methods of preventing the Glaser coupling is the protection of the alkyne group with a trimethylsilyl or triisopropylsilyl group. 93 However, this approach requires an additional protection/deprotection sequence, which has a low atom and time economy.…”
Section: Removal Of Copper Residues Aer Atrpmentioning
confidence: 99%
“…Therefore, a variety of postpolymerization modification procedures can be implemented following PISA including widely implemented click chemistries. For example, the emergence of copper­(I)-catalyzed azide–alkyne cycloaddition (CuAAC) click and thiol–ene click reactions has revolutionized the synthesis of functional polymer materials because of quantitative reaction conversions, mild reaction conditions, and orthogonality of functionalization using different click reactions. Herein, we have demonstrated that high-order morphologies can be obtained directly by using PhotoATR-PISA under ambient conditions simply via tailoring comonomer incorporation in core-forming segments.…”
Section: Introductionmentioning
confidence: 99%